Peningkatan Aktivitas dan Hasil Belajar Matematika Melalui Model Project Based Learning - Gustina, Gustina (Jurnal Didaktika Pendidikan Dasar, 2023)
The purpose of this research is to increase the activity and learning outcomes of mathematics by applying the project based learning model of group discussion methods in class V.A SDN 02 Payakumbuh. This type of research is Classroom Action Research carried out based on class action research steps with two cycles. The research data is in the form of test results, learning observations, field notes, and documentation of each learning improvement action. The source of research data is the process of learning activities from the researched subjects, namely teachers and students in class V.A, totaling 32 people. The results of this study can be seen from the recapitulation of the increased activity of students from pre-cycle to cycle II of 16.01%. Then experienced an increase of 18.02%. The learning outcomes of the knowledge aspect increased from 61.25 to 77.50 in cycle I, increased again to 88.75 in cycle II with an increase of 11.25%. The learning outcomes of the skills aspect obtained an average of 70.23 in pre-cycle, increasing to 82.50 in cycle II with an increase of 29.69%. It can be concluded that the application of the project based learning model in mathematics lessons can increase student activity and learning outcomes.